Geometrically modified auxetic polyurethane foams and their potential application in impact mitigation of masonry structures. (13th December 2021) - Asad, Mohammad; Zahra, Tatheer; Thambiratnam, David P.; Chan, Tommy H.T.; Zhuge, Yan
Highlights: Innovative Geometrically Modified Auxetic foam (GMAF) Structures are developed for impact mitigation. Incorporation of re-entrant shaped tubes and filaments enhanced the auxetic behaviour of PU foams. Significant energy dissipation is shown by the developed GMAF Structures. Application of GMAF to masonry provides impact mitigation. Ability of GMAF to prevent penetration of impactor into masonry wall is numerically proved. Abstract: Hollow block masonry buildings constructed alongside busy roads are vulnerable to vehicular impacts resulting in damage to property and harm to the building and vehicle occupants. This paper presents a method for the design and insertion of various forms of geometrically modified auxetic foam structures inside the hollow cores of block masonry walls for mitigating the adverse effects of such impacts. Due to the low tensile strength of masonry, the insertion material should possess high energy absorption characteristics and high strength for impact damage mitigation which can be achieved through auxetic foams with negative Poisson's ratio. To this end, finite element models of geometrically modified auxetic foams (GMAFs) are developed by inserting thin polyester sheets and hollow acrylonitrile butadiene styrene (ABS) tubes of various geometries into conventional polyurethane foams. The proposed geometrical configurations of inserted tubes and sheets result in auxetic behaviour of the conventional foam with a maximum negative Poisson's ratio of about −12. These foam models are validated analytically and then employed to model masonry walls with auxetic foam insertions in the hollow cores of blocks. These masonry wall models are then analysed under high-velocity lateral impacts. Results show the beneficial change in the failure mechanism of the masonry walls which altered from severe damage of wall face to the rebound of the impactor without penetration by reducing the displacement by four times, due to the presence of the auxetic foam insertions. This phenomenon occurred due to the significant energy dissipation caused by the combined effects of the re-entrant shaped hollow tubes and thin polyester sheet arrangements in the GMAF. Outcomes of this study will contribute towards safer masonry buildings along busy road fronts.